Scuba diving - Barrett, Norman S.; Burns, Rhoda; Burns, Robert (New York : F. Watts, 1988)
Color photographs, illustrations, and text describe scuba diving and the underwater world.
Includes index.
Booklist.
5.3
3-5.
3-6
Keywords: Scuba diving -- Juvenile literature; Scuba diving; Scuba diving